2007
DOI: 10.1590/s0074-02762007000300016
|View full text |Cite
|
Sign up to set email alerts
|

In vitro inhibition of Plasmodium falciparum by substances isolated from Amazonian antimalarial plants

Abstract: In the present study, a quassinoid, neosergeolide, isolated from the roots and stems of Picrolemma sprucei (Simaroubaceae), the indole alkaloids ellipticine and aspidocarpine, isolated from the bark of Aspidosperma vargasii and A. desmanthum (Apocynaceae), respectively, and 4-nerolidylcatechol, isolated from the roots of Pothomorphe peltata (Piperaceae), all presented significant in vitro inhibition (more active than quinine and chloroquine) of the multi-drug resistant K1 strain of Plasmodium falciparum. Neose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 52 publications
4
86
0
1
Order By: Relevance
“…The stabilisation of geographically specific populations of P. falciparum in continuous culture permits the evaluation of the actual susceptibility profiles to drugs and to natural products of the parasites that are in circulation in the human (and insect) populations in a given region (Andrade-Neto et al 2007). In the present study, it was possible to stabilise, in continuous culture, nine (16%) of 55 field isolates of P. falciparum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The stabilisation of geographically specific populations of P. falciparum in continuous culture permits the evaluation of the actual susceptibility profiles to drugs and to natural products of the parasites that are in circulation in the human (and insect) populations in a given region (Andrade-Neto et al 2007). In the present study, it was possible to stabilise, in continuous culture, nine (16%) of 55 field isolates of P. falciparum.…”
Section: Discussionmentioning
confidence: 99%
“…Patients presenting clinical symptoms related to severe malaria were invited to be enrolled in this study after confirmation of P. falciparum mono infection by thick smear diagnosis and their signing of an informed consent form (FMT-HVD Ethics in Research Commission 1838). Parasites were maintained in continuous culture using the method of Träger and Jensen (1976) with modifications, as described in Andrade-Neto et al (2007), using type A + human erythrocytes in RPMI-1640 medium (Sigma-Aldrich, St. Louis, MO, USA) supplemented with 10% A + human plasma (donated by blood banks). Cultures were maintained under an environment of 5% O 2 , 5% CO 2 and 90% N 2 and incubated at 37ºC.…”
Section: Determination Of Artemisinin In Toluene Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrapure water, obtained from a Milli-Q Plus System (Millipore, Bedford, MA, USA), was used in all analyses. 1 and 2 were isolated from P. sprucei as described previously 11,19 and used as reference standards. Their identity and purity were established based on 1D and 2D NMR, IR, HR-ESI-TOF-MS, HPLC-DAD and LC-ESI-MS analyses and comparison to literature data.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…There are a number of reports during the last few years mentioning several plant extracts possessing significant antimalarial activity and several active phytocompounds have also been initiated. de Andrade-Neto et al [36] reported quassinoid, neosergeolide isolated from the roots and stems of Picrolemma spruce (Simaroubaceae), the indole alkaloids ellipticine and aspidocarpine, isolated from the bark of Aspidosperma vargasii and Aspidosperma desmanthum (Apocynaceae), respectively and 4-nerolidylcatechol, isolated from the roots of Pothomorphe peltata (Piperaceae), have significant in vitro inhibition (more active than quinine and chloroquine) of the multi-drug resistant K1 strain of Plasmodium falciparum. Johns et al [37] isolated antimalarial compounds such as N-Nitrosoxylopine, Roemerolidine and Duguevalline from the extract of the bark of Annona squamosa.…”
Section: Discussionmentioning
confidence: 99%